Study on the relationship between working conditions and self-perceived psychological symptoms of the workforce in Malaysia / Nur Ismah Izzati Ismail - Nur Ismah Izzati, Ismail (2021)
There is limited research as to if working conditions such as decision latitude (e.g., skill discretion and decision authority), psychological job demands, job insecurity and social support (e.g., supervisor support and co-worker support) are perpetrators of perceived psychological symptoms such as depression, anxiety and stress in the workforce, thus the need for further empirical investigation. The objective of this study is to examine the relationship between the current working conditions and self-perceived psychological symptoms of the workforce (sewerage service sector) in Malaysia. The results have been obtained via – i) descriptive analysis – where the respondents’ sociodemographic profiles, respondents’ perceived working conditions through Job Content Questionnaire descriptive analysis and respondents’ self-perceived psychological symptoms through Depression Anxiety Stress Scales descriptive analysis have been described amicably; ii) Pearson Correlation test and, iii) Regression test used in assessing the relationships between JPP’s working conditions as well as their staffs’ psychological symptoms. Therefore, this study has shown statistically significant inverse relationship between the two (2) variables, wherein a significant regression equation was found for all three (3) psychological symptoms against working conditions accordingly; around 38% of the variance on depression; around 23.1% of the variance on anxiety; and around 34.6% of the variance on stress. It can be interpreted from the results found from regression analysis that job skill discretion is the most paramount significant predictor of all the psychological symptoms of workers in this study, as it cuts across the DASS scale of depression, anxiety and stress, negatively predicting them respectively.